MB1–MB2 Canal Orifice Distance in Maxillary First and Second Molars: - Sunaina (UNIVERSITY JOURNAL OF DENTAL SCIENCES, 2026)
Aim: To evaluate the distance between the mesiobuccal canal orifices (MB1 and MB2) in maxillary first and second molars in a Rajasthan population using cone beam computed tomography (CBCT).Materials and Methods: CBCT scans of maxillary first and second molars were evaluated in the axial plane at the level of the pulpal floor. The linear distance between the centers of the MB1 and MB2 canal orifices was measured using dedicated CBCT software. Measurements were statistically analyzed and comparisons were made between first and second molars and between genders.Results: The mean MB1–MB2 distance was 1.58 ± 0.72 mm in maxillary first molars and 1.97 ± 0.74 mm in maxillary second molars. The difference between first and second molars was statistically significant (p = 0.001). No statistically significant difference was observed between males and females (p = 0.923).Conclusion: Knowledge of MB1–MB2 inter-orifice distances in maxillary molars may assist clinicians in more predictable location of the MB2 canal and improve endodontic treatment outcomes.